Toward on-chip, in-cell recordings from cultured cardiomyocytes by arrays of gold mushroom-shaped microelectrodes - Fendyur, Anna; Spira, Micha E. (Frontiers in Neuroengineering, 2012)
Cardiological research greatly rely on the use of cultured primary cardiomyocytes (CM). The prime methodology to assess CM network electrophysiology is based on the use of extracellular recordings by substrate-integrated planar Micro-Electrode Arrays (MEAs). Whereas this methodology permits simultaneous, long-term monitoring of the CM electrical activity, it limits the information to extracellular field potentials (FP). The alternative method of intracellular action potentials (AP) recordings by sharp- or patch-microelectrodes is limited to a single cell at a time. Here, we began to merge the advantages of planar MEA and intracellular microelectrodes. To that end we cultured rat CM on micrometer size protruding gold mushroom-shaped microelectrode (gMµE) arrays. Cultured CMs engulf the gMµE permitting FPs recordings from individual cells. Local electroporation of a CM converts the extracellular recording configuration to attenuated intracellular APs with shape and duration similar to those recorded intracellularly. The procedure enables to simultaneously record APs from an unlimited number of CMs. The electroporated membrane spontaneously recovers. This allows for repeated recordings from the same CM a number of times (>8) for over 10 days. The further development of CM-gMµE configuration opens up new venues for basic and applied biomedical research.